Experimental Manipulation Shows a Greater Influence of Population than Dietary Perturbation on the Microbiome of Tyrophagus putrescentiae - Erban, Tomas; Ledvinka, Ondrej; Nesvorna, Marta; Hubert, Jan (Applied and environmental microbiology, 2017)
Tyrophagus putrescentiae is inhabited by bacteria that differ among mite populations (strains) and diets. Here, we investigated how the microbiome and fitness of Tputrescentiae are altered by dietary perturbations and mite populations. Four T. putrescentiae populations, referred to as dog, Koppert, laboratory, and Phillips, underwent a perturbation, i.e., a dietary switch from a rearing diet to two experimental diets. The microbiome was investigated by sequencing the V1-V3 portion of the 16S rRNA gene, and selected bacterial taxa were quantified by quantitative PCR (qPCR) using group/taxon-specific primers. The parameters observed were the changes in mite population growth and nutritional status, i.e., the total glycogen, lipid, saccharide, and protein contents in mites. The effect of diet perturbation on the variability of the microbiome composition and population growth was lower than the effect induced by mite population. In contrast, the diet perturbation showed a greater effect on nutritional status of mites than the mite population. The endosymbionts exhibited high variations among T. putrescentiae populations, including Cardinium in the laboratory population, Blattabacterium-like bacteria in the dog population, and Wolbachia in the dog and Phillips populations. Solitalea-like and Bartonella-like bacteria were present in the dog, Koppert, and Phillips populations in different proportions. The T. putrescentiae microbiome is dynamic and varies based on both the mite population and perturbation; however, the mites remain characterized by robust bacterial communities. Bacterial endosymbionts were found in all populations but represented a dominant portion of the microbiome in only some populations.IMPORTANCE We addressed the question of whether population origin or perturbation exerts a more significant influence on the bacterial community of the stored product mite Tyrophagus putrescentiae The microbiomes of four populations of T. putrescentiae insects subjected to diet perturbation were compared. Based on our results, the bacterial community was more affected by the mite population than by diet perturbation. This result can be interpreted as indicating high stability of the putative intracellular symbionts in response to dietary perturbation. The changes in the absolute and relative numbers of Wolbachia, Blattabacterium-like, Solitalea-like, and Cardinium bacteria in the T. putrescentiae populations can also be caused by neutral processes other than perturbation. When nutritional status is considered, the effect of population appeared less important than the perturbation. We hypothesize that differences in the proportions of the endosymbiotic bacteria result in changes in mite population growth.
Keywords: Solitalea; Gastrointestinal Microbiome; stravovací zvyklosti; DNA bakterií; symbiont; DNA, Ribosomal; Diet; Sequence Analysis, DNA; RNA ribozomální 16S; Acaridae; Cluster Analysis; zvířata; RNA, Ribosomal, 16S; fitness; sekvenční analýza DNA; DNA, Bacterial; Blattabacterium; Wolbachia; Bartonella; 16S rRNA; dieta; feeding; shluková analýza; Real-Time Polymerase Chain Reaction; ribozomální DNA; Tyrophagus putrescentiae; střevní mikroflóra; Bacteria; Animals; bacteria; Feeding Behavior; Cardinium; kvantitativní polymerázová řetězová reakce